2014
DOI: 10.9734/jsrr/2014/10693
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge, Attitudes and Practices towards Exercise among Women Attending Antenatal Care at the University Teaching Hospital in Lusaka, Zambia

Abstract: Introduction:There is persuasive evidence on the benefits of exercise during pregnancy such as; reduced time spent in labour, prevention of caesarean sections, quick recovery after childbirth and getting back to the pre-pregnancy figure. The aim of the study was to obtain information on the knowledge, attitudes and practices towards exercise among women attending antenatal care at the University Teaching Hospital in Lusaka, Zambia. Methods: This was a cross-sectional exploratory study. Data was collected using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 3 publications
2
16
6
Order By: Relevance
“…Therefore, a large group of respondents seems to have a negative attitude towards ANEx in pregnancy. This nding is below par with the recent studies that have reported a positive prototype shift in attitudes toward exercise among pregnant women globally over the past two decades [9][10][11]31]. This study found that attitude towards exercise in pregnancy was mostly in uenced by concerns about fetal safety, cultural constraints, lack of family support, and insu cient information about ANEx.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…Therefore, a large group of respondents seems to have a negative attitude towards ANEx in pregnancy. This nding is below par with the recent studies that have reported a positive prototype shift in attitudes toward exercise among pregnant women globally over the past two decades [9][10][11]31]. This study found that attitude towards exercise in pregnancy was mostly in uenced by concerns about fetal safety, cultural constraints, lack of family support, and insu cient information about ANEx.…”
Section: Discussioncontrasting
confidence: 52%
“…A structured knowledge, attitude, and practice (KAP) ANEx questionnaire (Additional le 1) was used for data collection. The questions to be included in the instrument were adapted from previous studies conducted in Brazil, Nigeria, Zambia, American Pregnancy Association top recommended exercises (APA), and ACOG recommendations [9,17,28,29]. The questionnaire requested information on the sociodemographic, maternal characteristics, their knowledge concerning ANEx, need for ANEx during pregnancy, and barriers to ANEx.…”
Section: Data Collection Tool and Methodsmentioning
confidence: 99%
See 3 more Smart Citations